2020
DOI: 10.35808/ijeba/540
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Mediated Associations among Audit Quality, Earnings Quality, and Share Price: The Case of Jordan

Abstract: Purpose: The current study aims to investigate the relationship between audit quality and the share price in Jordan as a developing market. Moreover, it also uses the role of earnings quality as a mediator factor in the study model. Design/Approach/Methodology: The study sample is comprised of all Jordanian industrial public shareholding companies listed in Amman Stock Exchange during the years 2010 to 2018. Therefore, this study uses a panel data analysis on financial disclosures. Findings: The study conclude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…This means that the sound managerial practices or behavior will lead to increase the company's performance. From the back drop, these findings are following empirical studies, such as Latif et al (2017), DeFond et al (2007, Wysocki (2005), Larson andResutek (2011), Leuz et al (2003), Dechow et al (2010), Antonio et al (2019) and Afifa et al (2020). These studies indicated that market return is positively affected by EQ, and it plays a vital role by increasing the market value of share prices.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…This means that the sound managerial practices or behavior will lead to increase the company's performance. From the back drop, these findings are following empirical studies, such as Latif et al (2017), DeFond et al (2007, Wysocki (2005), Larson andResutek (2011), Leuz et al (2003), Dechow et al (2010), Antonio et al (2019) and Afifa et al (2020). These studies indicated that market return is positively affected by EQ, and it plays a vital role by increasing the market value of share prices.…”
Section: Discussionsupporting
confidence: 55%
“…Mehrani et al (2017) discussed that we can measure the EQ by earnings response coefficient, discretionary accruals, predictive value of earnings, conservatism, and real earnings management. Ali et al (2011), Jafari (2016, Alsufy et al (2020) and Afifa et al (2020) suggested that the cash approach uses EQ as a measurement. They documented that the closeness of the accounting profits and cash reflects a high quality, and this measurement was adopted in the current study.…”
Section: Measurements Of the Study Variablesmentioning
confidence: 99%
“…One of the most momentous tools used by a board of directors to supervise management activities and choices as regards financial reporting has long been renowned as auditor qualities (Abubakar et al, 2020;Bala et al, 2018;Ihsan et al, 2016). Earlier research on AAT and FRQ has yielded conflicting results (Hay, 2012;Trotman, 2013;Aswadi et al, 2014;Tepalagul & Lin, 2015;Kamolsakulchai, 2015;Lin et al, 2017;Ndubuisi & Ezechukwu, 2017;Badawy & Aly, 2018;Abubakar et al, 2020;Afifa et al, 2020;Akono, 2020;Suleiman et al, 2020). These mixed results could be attributable to variances in the setting and the procedures used in these investigations.…”
Section: Auditor Attributes and Financial Reporting Qualitymentioning
confidence: 99%
“…On the other hand, extraordinarily little evidence was set up between auditor size AS and FRQ (Hay, 2012;Umaru, 2014;Lin et al, 2017;Afifa et al, 2020), none-audit service fees NASF, (Mgbame, Izedonmi et al, 2012;Patrick et al, 2017;Ugwunta et al, 2018), suggesting more investigation is needed in this area of study. As a result, other attributes of auditors' such as auditor firm age, auditor tangibility, auditor responsiveness, auditor reliability, auditor assurance, auditor empathy and client financial health (Gaynor et al, 2016), need to be studied and re-evaluated further for better inspection of FRQ.…”
Section: Ejmssmentioning
confidence: 99%
See 1 more Smart Citation